BIMBINGAN TEKNIS PEMBUATAN ASAP CAIR DI GAPOKTAN RINGIN ASRI KECAMATAN SUMBERMANJING WETAN - Mochammad Agung Indra Iswara; Asalil Mustain; Prayitno Prayitno; Anang Takwanto (Jurnal Pengabdian kepada Masyarakat, 2026)
The Ringin Asri Farmers Group (GAPOKTAN) in Kedungbanteng Village, Sumbermanjing Wetan District, Malang Regency faces a challenge in managing coconut waste, which tends to accumulate in large quantities and poses potential environmental risks. One proposed solution is processing the waste through pyrolysis at 600°C in the absence of oxygen, followed by a condensation stage to convert the resulting smoke into liquid smoke. This product offers multiple benefits, including reducing biomass waste and air pollution, as well as serving as a natural food preservative, pesticide, and plant antibacterial agent. Through a Community Service Program (PPM), the Department of Chemical Engineering, State Polytechnic of Malang, conducted technical training on liquid smoke production for GAPOKTAN members using lectures, group discussions, and hands-on demonstrations. The activity was met with high enthusiasm, and participants were able to easily understand the production process. This program is expected to enhance the group’s skills in utilizing coconut waste to produce natural preservatives, increase their economic potential, and reduce coconut waste generation in the area.